Analysis of Ethylene Propene Cargo Loss During Discharge Using Root Cause Analysis - Zulfaidah Ariany; Muhammad Alif Fadhil Rizqi; Halim T Cahyono; Arwen Surya A Anjalu (International Journal of Marine Engineering Innovation and Research, 2026)
The transfer of ethylene-propene cargo from LPG/C vessels to onshore storage tanks is a critical operation in which measurement accuracy, temperature correction, and transfer system efficiency influence cargo integrity. This study analyses cargo loss during the discharge process using quantitative calculations and Root Cause Analysis (RCA). Cargo quantity was determined by calculating the apparent liquid volume (13,465.454 KL) from tank sounding data, followed by temperature correction using the shrinkage factor equation 1+α(t−T) with ? = 0.0000348. The corrected liquid volume obtained was 13,463.632 KL. Using an average density of 561.1 kg/m³, the calculated liquid mass reached 7,598.525 MT. Vapour volume was obtained by subtracting the liquid volume from the total tank capacity, producing 3,027.235 KL, which, after thermal correction, became 3,026.339 KL. With a gas factor of 0.0200851, the vapour mass was calculated as 59.207 MT, resulting in a total cargo mass of 7,657.732 MT. Comparison between ship and shore tank measurements showed a discrepancy of 78.482 MT or −2.294%, indicating cargo loss during transfer. RCA results identified suboptimal vapour return systems and temperature-induced density variations as dominant causes. Recommended improvements include optimising vapour recovery performance, implementing Automatic Tank Gauge (ATG) systems, and standardising temperature-corrected cargo calculations.